IMPLEMENTASI CITIZEN’S CHARTER TERHADAP KUALITAS PELAYANAN PUBLIK DI PROVINSI DI ACEH - Amirulkamar, Said; Salwa, Wan Nurus (TheJournalish: Social and Government, 2024)
This research aims to analyze the impact of the Citizen Charter (Service Contract) on the quality of public services in Aceh. The research method used is qualitative with a descriptive approach. Research data was obtained through scientific journals, literature reviews, and other trusted sources. The research results show that the implementation of the Citizen Charter in Aceh is still in the developing stage, with several significant advances in several sectors, such as the establishment of public service malls (MPP) and improving the quality of services at the Population and Civil Registration Service (Disdukcapil). Even though there has been positive progress, there are still several shortcomings that need to be addressed, such as a lack of socialization and coordination between agencies. This research recommends several steps to improve the implementation of the Citizen Charter in Aceh, including increasing outreach and actively involving the community.